Shock wave technology and application: an update - Rassweiler, Jens; Knoll, Thomas; Köhrmann, Kai-Uwe; McAteer, James A.; Lingeman, James E.; Cleveland, Robin O.; Bailey, Michael R.; Chaussy, Christian (European urology, 2011)
Context - The introduction of new lithotripters has increased problems associated with shock wave application. Recent studies concerning mechanisms of stone disintegration, shock wave focusing, coupling, and application have appeared that may address some of these problems. - Objective - To present a consensus with respect to the physics and techniques used by urologists, physicists, and representatives of European lithotripter companies. - Evidence acquisition - We reviewed recent literature (PubMed, Embase, Medline) that focused on the physics of shock waves, theories of stone disintegration, and studies on optimising shock wave application. In addition, we used relevant information from a consensus meeting of the German Society of Shock Wave Lithotripsy. - Evidence synthesis - Besides established mechanisms describing initial fragmentation (tear and shear forces, spallation, cavitation, quasi-static squeezing), the model of dynamic squeezing offers new insight in stone comminution. Manufacturers have modified sources to either enlarge the focal zone or offer different focal sizes. The efficacy of extracorporeal shock wave lithotripsy (ESWL) can be increased by lowering the pulse rate to 60-80 shock waves/min and by ramping the shock wave energy. With the water cushion, the quality of coupling has become a critical factor that depends on the amount, viscosity, and temperature of the gel. Fluoroscopy time can be reduced by automated localisation or the use of optical and acoustic tracking systems. There is a trend towards larger focal zones and lower shock wave pressures. - Conclusions - New theories for stone disintegration favour the use of shock wave sources with larger focal zones. Use of slower pulse rates, ramping strategies, and adequate coupling of the shock wave head can significantly increase the efficacy and safety of ESWL.